Driving forces for covalent assembly of porphyrins by selective C-H bond activation and intermolecular coupling on a copper surface - Floris, Andrea; Haq, Sam; Veld, Mendel In't; Amabilino, David A.; Raval, Rasmita; Kantorovich, Lev (American Chemical Society, 2016)
Recent synthesis of covalent organic assemblies at surfaces has opened up the promise of producing robust nanostructures for functional interfaces. To uncover how this new chemistry works at surfaces and understand the underlying mechanism(s) that control bond-breaking and bond-making processes at specific positions of the participating molecules, we study here the coupling reaction of tetra(mesityl)porphyrin molecules, which creates covalently connected networks on the Cu(110) surface by utilising the 4-methyl groups as unique connection points. Using scanning tunneling microscopy (STM), state-of-the-art density functional theory (DFT) and Nudged Elastic Band (NEB) calculations, we show that the unique directionality of the covalent bonding is found to stem from a chain of highly selective C-H activation and de-hydrogenation processes, followed by specific intermolecular C-C coupling reactions that are facilitated by the surface, by steric constraints and by anisotropic molecular diffusion. These insights provide the first steps towards developing synthetic rules for complex two-dimensional covalent organic chemistry that can be enacted directly at a surface to deliver specific macromolecular structures designed for specific functions.